Examining the Relationship between Teaching Practice Exercise (TPE) and Teachers’ Competency (TC) - SABITU, Kamoru Abiodun (Researchparks Publishing, 2023)
The study examined the relationship between teaching practice exercise and teachers competency. This study adopted a correlational research design of survey method. The population of this study involved all mathematics teachers in the Public secondary schools in Afijio Local Government Area, Oyo State, Nigeria. The Local Government under study comprises of twenty eight (28) public secondary schools with at least two (2) mathematics teachers in each of the schools. The twenty-eight (28) Public secondary schools were chosen as sample schools while two (2) mathematics teachers were purposely selected from each schools as respondents to make fifty-six (56) respondents. The instrument used for this study was a self-structured questionnaire tagged “Teaching Practice Exercise and Teachers Competencies (TPETC). Three hypotheses were stated and tested at 0.05 level of significance. The instrument was validated by experts. The instrument has the reliability coefficient of 0.83. Data collected were analysed using Pearson Product Moment Correlation (PPMC). The findings showed that that there is a relationship between teaching practice exercise and teachers’ academic competence among Mathematics Teachers; there is a relationship between teaching practice exercise and teachers’ professional competence among Mathematics Teachers and there is a relationship between teaching practice exercise and teachers’ personal competence among Mathematics Teachers in Afijio Local Government Area. Based on the findings of the study, it was recommended among others that adequate orientation should be provided to the pre-service teachers to know that the competencies are important and integral part of their career and personal lives.